KINEMATIC INTERACTION EFFECTS ON DYNAMIC RESPONSE OF HIGH-RISE BUILDINGS WITH SUBSURFACE STRUCTURES - Kurniawandy A.; Harahap M. I. H.; Yusa M. (GEOMATE Journal, 2025)
High-rise buildings in urban areas face significant seismic challenges due to interactions between the structure, foundation, and surrounding soil. One key component is the kinematic aspect of Soil–Structure Interaction (SSI), which alters the seismic motion transmitted to the foundation, particularly for buildings with basements. This study investigates the effect of kinematic SSI on the seismic response of high-rise buildings with basement structures using linear time-history analysis. Two site classes based on soil stiffness—SD (medium soil) and SE (soft soil)—are analyzed to evaluate how kinematic interaction influences base shear and displacement. Results show that in site class SD, the reduction in response is minimal. However, in site class SE, where soil stiffness is lower, kinematic effects lead to substantial decreases in both base shear and displacement. Basement embedment depth also plays a role in modifying seismic input. These findings emphasize the importance of including kinematic interaction in seismic analysis to achieve safer, more efficient structural designs, especially in soft-soil conditions.